Utah Foreign Language Guide - Howe, Elliot C.; Utah State Board of Education, Salt Lake City. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1966)
This guide presents an analysis and rationale of foreign language programs in elementary and secondary schools, stressing development of cultural understanding through language instruction in the basic skills of the target language. Major sections cover: (1) purposes of foreign language instruction; (2) contributing disciplines--psychology, linguistics, and culture; (3) methods of instruction--basic skills, audiovisual aids, lesson plans, interdisciplinary studies, and textbook selection; (4) program materials; (5) equipment; (6) innovations; (7) program evaluation; and (8) professional staff. A selected bibliography is included. (RL)
ERIC Note: Preliminary edition.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Instruction; Cultural Education; Cultural Enrichment; Curriculum Guides; Educational Objectives; Educational Philosophy; Fles; Foreign Culture; Instructional Program Divisions; Interdisciplinary Approach; Language Programs; Modern Languages; Program Content; Second Language Learning; Secondary Schools; Teaching Guides; Teaching Methods